IER3 Promotes Expansion of Adipose Progenitor Cells in Response to Changes in Distinct Microenvironmental Effectors. (13th May 2015) - Ravaud, Christophe; Esteve, David; Villageois, Phi; Bouloumie, Anne; Dani, Christian; Ladoux, Annie
Abstract Adipose tissue expansion is well‐orchestrated to fulfill the energy demand. It results from adipocyte hypertrophy and hyperplasia due to adipose progenitor cell (APC) expansion and differentiation. Chronic low grade inflammation and hypoxia take place in obese adipose tissue microenvironment. Both of these events were shown to impact the APC pool by promoting increased self‐renewal along with a decrease in the APC differentiation potential. However, no common target has been identified so far. Here we show that the immediate early response 3 gene (IER3) is preferentially expressed in APCs and is essential for APC proliferation and self‐renewal. Experiments based on RNA interference revealed that impairing IER3 expression altered cell proliferation through ERK1/2 phosphorylation and clonogenicity. IER3 expression was induced by Activin A, which plays a crucial role in adipocyte differentiation as well as by a decrease in oxygen tension through HIF1‐induced transcriptional activation. Interestingly, high levels of IER3 were detected in native APCs (CD34+/CD31− cells) isolated from obese patients and conditioned media from obese adipose tissue‐macrophages stimulated its expression. Overall, these results indicate that IER3 is a key player in expanding the pool of APC while highlighting the role of distinct effectors found in an obese microenvironment in this process. Stem Cells2015;33:2564–2573